ANALYSIS OF ENGLISH â€“ INDONESIAN TRANSLATION METHOD IN TRANSLATING METAPHOR IN THE VANISHED MAN NOVEL - Kurniawan, Ade Danu; Rosnija, Eni; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The research investigatedthe translation methods used by Sendra B. Tanuwidjaja to translate the metaphors in the Vanished Man Novel by Jeffrey Deaver translated as Si Perapal. This was an analysis descriptive research. There were three chapters out of 52 chapters that were analyzed.There were 30 metaphorical sentences taken from those three chapters. The data were collected by analysis of document. Based on the research findings, from 30 metaphors, 16 metaphors (52.90%) were translated literally, five metaphors (16.50%) were translated with addition, and nine metaphors (29.70%) were translated freely.To conclude, Sendra B. Tanuwidjaja as the translator followed the common pattern of translation where as he tried to emphasize the use of literal translation and made translation equivalence. Key words: Metaphor, Translation of Metaphor, Translation Equivalence Abstrak: Penelitian ini menginvestigasi metode terjemahan yang digunakan oleh Sendra B. Tanuwidjaja untuk menerjemahkan metaphor dalam novel Vanished Man yang dikarang oleh Jeffrey Deaver diterjemahkan sebagai Si Perapal. Penelitian ini adalah penelitian deskriptif. Terdapat tiga dari 52 bab yang dianalisis. Terdapat 30 kalimat metaphor yang diambil dari ketiga bab tersebut. Data dikumpulkan melalui analasis dokumen. Berdasarkan temuan penelitian, dari 30 kalimat metaphor, 16 metapor (52,9%) diterjemahkan dengan literal translation, lima metapor (16,5%) diterjemahkan dengan translation with addition, dan Sembilan metaphor (29,7%) diterjemahkan dengan free translation. Â  Kata Kunci: Metaphor, Terjemahan Metapor, Kesetaraan Terjemahan Â